Fabulous science : fact and fiction in the history of scientific discovery - Waller, John, 1972- (Oxford University Press, 2002)
The great biologist Louis Pasteur suppressed data that didn't support the case he was making. Albert Einstein's theory of general relativity was only 'confirmed' in 1919 because an eminent British scientist massaged his figures. Joseph Lister's famously spotless hospital wards were actually notoriously dirty. Gregor Mendel, supposed father of the science of heredity, never grasped the fundamental principles of 'Mendelian' genetics. The history of science used to be presented as a heroic saga, in which a few far-seeing geniuses overcame the petty opposition of lesser minds to establish new scientific truths. But over recent decades, historians of science have cast a much more critical eye over their subject. Delving into laboratory notebooks and reconstructing once-fierce debates, they have challenged many of our basic assumptions about the nature of science and the roles its greatest heroes played. Fabulous Science reveals many of these findings to the general reader for the first time.; Often startling and always enthralling, they show that some of our most important scientific theories were initially accepted only because famous scientists fudged data, pulled rank, or were propped up by religious and political elites. Striking case-studies show that science is not always driven on by pure rationality: human factors can play at least as big a role in the origin and reception of scientific ideas. Even poorly attested theories can gain widespread acceptance if put forward by scientists with sufficient clout. The new history of science also demonstrates that many standard portraits of scientific heroes are little more than romantic inventions. Classic accounts of men before their time who battled to overcome ignorant opposition before achieving scientific immortality exaggerate the originality of the few and underplay the crucially important contributions of the many. Fabulous Science argues that our view of the history of science has been egregiously distorted by individuals seeking to glorify disciplines and nations, and by famous scientists who unfairly garnered credit properly due to others.; Fabulous Science restores to the history of science its complex personalities, bitter rivalries, and intense human dramas which until recently have been overlain by sanitising myths and misconceptions. Above all, its richly entertaining vignettes will transform the way we think about science, past, present, and future.